Functional Metagenomics: Tools and Applications - Charles, Trevor C.; Liles, Mark R.; Sessitsch, Angela (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, the latest tools available for functional metagenomics research are described.This research enables scientists to directly ac cess the genomes from diverse microbial genomes at one time and study t hese "metagenomes". Using the modern tools of genome sequencing and clo ning, researchers have now been able to harness this astounding metagen omic diversity to understand and exploit the diverse functions of micro organisms. Leading scientists from around the world demonstrate how the se approaches have been applied in many different settings, including a quatic and terrestrial habitats, microbiomes, and many more environment s. This is a highly informative and carefully presented book, providing microbiologists with a summary of the latest functional metagenomics l iterature on all specific habitat.
Section I. Tools for Functional Metagenomics -- Prologue -- 1) Next- generation sequencing in Functional Metagenomics -- 2) Cloning systems -- 3) Expression systems -- 4) Hosts for heterologous expression -- 5) Bioinformatic tools for functional metagenomics -- 6) Screening and selection for expressed functions -- 7) Synthetic biology approaches for functional metagenomics -- Section II. Applications in Functional M etagenomics -- 8) Enzyme discovery -- 9) Metabolite discovery -- 10) C substrate utilization (with SIP) -- 11) Genome Assembly and Functio nal Annotation -- 12) Aquatic ecosystems -- 13) Terrestrial ecosystem s -- 14) Aeromicrobiology -- 15) Animal microbiomes -- 16) Human mic robiomes -- 17) Plant microbiomes -- 18) Biofilms -- 19) Extreme envir onments -- 20) Wastewater -- 21) Food microbiology -- Epilogue: Futur e prospects in functional metagenomics.
Description based on publisher-supplied MARC data.
Keywords: Microbial ecology; Microbial genetics; Microbial genomics; Microbiology; Microbial Genetics and Genomics; Applied Microbiology; Microbial Ecology